SUMBER INFORMASI TENTANG DETEKSI DINI KANKER SERVIX PADA WANITA PASANGAN USIA SUBUR - Rahmawati, Agustin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: SOURCE OF INFORMATION ABOUT EARLY DETECTION OF CANCER CERVIX IN WOMEN OF CHILDBEARING COUPLES AGE <20 YEARS NORTH SEMARANG DISTRICT  SEMARANG CITY. Cervical cancer is a important health problem for women around the world. This cancer is the second most common in women and affects more than 1.4 million women worldwide.  Every year, more than 460,000 cases occurred and approximately 231,000 (50.2%) women died of the cancer disease.  This research to know source of information about early detection of cancer cervix in women of childbearing couples age <20 years north semarang district semarang city. This research is a descriptive study. This study used cross sectional approach or cross-sectional study. The population in this study is a Women <20 years in the district of North Semarang as many as 155 people. This study used purposive sampling with a sample of 132. This study used a questionnaire instrument. Descriptive statistics will be used to determine the frequenc. The results showed 67.4% of respondents have received information on the early detection of cervix cancer and 32.6% of respondents did not received information about early detection of cervix cancer. The majority of couples of reproductive age women in the District of North Semarang Semarang already get information about early detection of cervix cancer.  Key Word: Source of Information, Woman of childbearing couple, Early Detection of Cancer Cervix